(untitled) (Signos do Consumo, 2023)
This article aims to develop theoretical and practical considerations, based on empirical data, on the use of ChatGPT as a campaign creation tool. Calibrating our research perspective, we initially discuss the bases of advertising creation processes and unravel the logic of generative artificial intelligence. Moving on to experience, we used ChatGPT to design Christmas campaigns for Coca-Cola. As a result, we highlight some of the main limitations and potential of this platform for advertising creativity.